Nutritional intake of opioid replacement therapy patients in community pharmacies: A pilot study. Issue 3 (28th April 2015) - Waddington, Freya; Naunton, Mark; Kyle, Greg; Cooper, Gabrielle
Abstract Aim Opioid replacement therapy (ORT) is an established therapy for a patient group that has been associated with nutrition‐related comorbidities. This paper aims to assess the nutritional intake and supplementation in ORT patients, determine the extent of nutritional/dietary advice supplied to ORT patients and to briefly examine patients' perception of pharmacists' provision of nutritional advice. Methods The nutritional intake of ORT patients receiving treatment in community pharmacies within the Australian Capital Territory was assessed via a 24‐hour recall survey. Food intake data were analysed via nutrient analysis software and compared with Australian Nutrition Reference Values and the nutrient intakes of the Australian population. Patients were surveyed to determine supplement use and perceptions of nutritional advice gained by pharmacists. Results Potential insufficient intake of various macronutrients and micronutrients was observed in both sexes. Less than 25% of patients recorded supplement use. Fifteen percent of males and 21% of females stated that they had approached a pharmacist with a nutrition‐related query. All patients who received nutritional advice followed the advice. Conclusions ORT patients dosing at community pharmacies appear to have poor nutritional intake. ORT patients appear to be receptive to pharmacist's advice. Community pharmacists can potentially increase the beneficial health outcomes in this population through the proactive supply of accurate nutritional advice.